Flexible piezoelectric nano-composite films for kinetic energy harvesting from textiles. (March 2017) - Almusallam, Ahmed; Luo, Zhenhua; Komolafe, Abiodun; Yang, Kai; Robinson, Andrew; Torah, Russel; Beeby, Steve
Abstract: This paper details the enhancements in the dielectric and piezoelectric properties of a low-temperature screen-printable piezoelectric nano-composite film on flexible plastic and textile substrates. These enhancements involved adding silver nano particles to the nano-composite material and using an additional cold isostatic pressing (CIP) post-processing procedure. These developments have resulted in a 18% increase in the free-standing piezoelectric charge coefficient d33 to a value of 98 pC/N. The increase in the dielectric constant of the piezoelectric film has, however, resulted in a decrease in the peak output voltage of the composite film. The potential for this material to be used to harvest mechanical energy from a variety of textiles under compressive and bending forces has been evaluated theoretically and experimentally. The maximum energy density of the enhanced piezoelectric material under 800 N compressive force was found to be 34 J/m 3 on a Kermel textile. The maximum energy density of the enhanced piezoelectric material under bending was found to be 14.3 J/m 3 on a cotton textile. These results agree very favourably with the theoretical predictions. For a 10x10 cm piezoelectric element 100 µm thick this equates to 38 μJ and 14.3 μJ of energy generated per mechanical action respectively which is a potentially useful amount of energy. Graphical abstract: Highlights: Adding silver nano particles to a polymer piezoelectric matrix improves d33 by 18%. Energy harvesting potential of nano-composite film on different textiles explored. Tens of microwatts harvested per bending or compressive action. Theoretically calculated and measured energy densities in good agreement.